LUFFA ACUTANGULA SEBAGAI ALTERNATIF PENURUN KADAR GLUKOSA DARAH - Joko Sigit (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: To determine the effect of Luffa Acutangula to reduce blood glucose level.Methods: It used literature review method. It identification publication articles since October 2006 to October 2015 using keywords oyong, luffa acutangula, and diabetes mellitus..Results: Result of identifaction found three articles that discuss about effect and composition of luffa acutangula. Conclusion: Oyong (Luffa Acutangula) had curcubitacin and flavonoid that have hipoglikemic effect. Those two compounds can prevent increasing of blood glucose.